Sistem Pendukung Keputusan Penentuan Penempatan Guru SMP Pada Proses Mutasi Guru - Jeperson Hutahaean; Jhonson Efendi Hutagalung (TIN: Terapan Informatika Nusantara, 2023)
The Asahan District education office requires a decision-based system application that can determine the location of teacher transfers. To design and build a decision-making system for determining the placement of junior high school teachers in the teacher transfer process in Asahan Regency. This system can help Regional Leaders as decision makers to weigh and determine a teacher candidate who is eligible to occupy a school location from several alternative teacher candidates who meet the criteria. Data was analyzed using the AHP (Analytic Hierarchy Process) method. This application is designed using the Visual Basic 6.0 programming language using the Microsoft Access database and Crystal Report as a report which is a support for the process of designing this system. The report produced by this system is a report on the results of the selection of teachers who will be transferred